Joseph von Gerlach—A Reminder of One of the Pioneers of Histochemistry on the Occasion of His 200th Birthday. (October 2020) - Weyers, Wolfgang
Abstract : Abstract: Joseph von Gerlach was an eminent German anatomist and pioneer of histology. He devised various techniques to assess the fine structure of tissues, most notably a procedure of staining histologic sections that marked the beginning of routine staining in histology. Gerlach was also one of the pioneers of microphotography.